2021
DOI: 10.1186/s40478-021-01242-2
|View full text |Cite
|
Sign up to set email alerts
|

Disease-, region- and cell type specific diversity of α-synuclein carboxy terminal truncations in synucleinopathies

Abstract: Synucleinopathies, including Parkinson’s disease (PD), Lewy body dementia (LBD), Alzheimer’s disease with amygdala restricted Lewy bodies (AD/ALB), and multiple system atrophy (MSA) comprise a spectrum of neurodegenerative disorders characterized by the presence of distinct pathological α-synuclein (αSyn) inclusions. Experimental and pathological studies support the notion that αSyn aggregates contribute to cellular demise and dysfunction with disease progression associated with a prion-like spread of αSyn agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…It is preferentially propagated in oligodendrocytes despite their lower αSyn expression levels due to a favorable cleavage environment that produces the more potent strains. Aberrant protease activities in MSA could exacerbate this process, but this should be confirmed by future experiments [41]. Both soluble and insoluble fractions of MSA extracts have robust seeding activity, while only the insoluble fraction of PD extracts displayed seeding activity.…”
Section: Prion-like Properties Of αSynmentioning
confidence: 85%
See 2 more Smart Citations
“…It is preferentially propagated in oligodendrocytes despite their lower αSyn expression levels due to a favorable cleavage environment that produces the more potent strains. Aberrant protease activities in MSA could exacerbate this process, but this should be confirmed by future experiments [41]. Both soluble and insoluble fractions of MSA extracts have robust seeding activity, while only the insoluble fraction of PD extracts displayed seeding activity.…”
Section: Prion-like Properties Of αSynmentioning
confidence: 85%
“…Carboxy truncations of αSyn promote both its aggregation and toxicity [61]. Specific carboxy truncated forms of αSyn have been detected by immunostaining with antibodies that specifically react with their precise forms showing their specific distribution [41]. In DLB, neuronal inclusions in the SN and amygdala were positive for αSyn cleaved after residues 103, 119, 122, and 125, whereas in MSA GCIs αSyn truncated at residues 103, 115, 119, and 125 were present.…”
Section: Self-propagation Of Prionoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, larger case-cohort studies are warranted including validation and quantification using other techniques such as specific ELISAs. A recent study has elegantly demonstrated diversity of -synuclein C-terminal truncations in discriminating different synucleinopathies [40]. By continuing to interrogate human post-mortem tissue pathology using novel -synuclein antibodies, our understanding of disease pathogenesis will increase profoundly and may also pose as a basis of both biomarker (prognostic and diagnostic) and therapeutic discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, larger case-cohort studies are warranted including validation and quantification using other techniques such as specific ELISAs. A recent study has elegantly demonstrated diversity of a-synuclein C-terminal truncations in discriminating different synucleinopathies [40]. By continuing to interrogate human post-mortem tissue pathology using novel a-synuclein antibodies, our understanding of disease pathogenesis will increase profoundly and may also pose as a basis of both biomarker (prognostic and diagnostic) and therapeutic discoveries.…”
Section: Discussionmentioning
confidence: 99%